On the Error and Outage Performance of Decode-and-Forward Cooperative Selection Diversity System With Correlated Links - Swaminathan, Ramabadran (2017)
A cooperative diversity system improves the communication reliability and throughput in a multipath fading environment with the help of relay nodes. We consider a cooperative diversity system with a source (S), a decode-and-forward relay (R), and a selection-combining-enabled destination (D). In this paper, we derive the exact end-to-end symbol error probability (SEP) for -ary phase-shift keying (MPSK) signaling using a paired error approach and differential binary phase-shift keying (DBPSK) signaling over correlated, nonidentical, slow, and flat Nakagami- fading channels by assuming the correlation between SD–RD, SR–SD, and SR–RD fading channels. In addition, we perform the exact outage probability analysis for the same scenario. Furthermore, we provide the asymptotic expressions for SEP and outage probability by removing the infinite-series terms to investigate the diversity order. In a nutshell, the numerical results reveal that the SR–RD correlated channel scenario outperforms the uncorrelated channel scenario in terms of SEP. In addition, SEP performance degradation is observed in the case of other correlated channel scenarios compared with the uncorrelated channel scenario. Moreover, marginal performance improvement in outage probability is observed in the low-signal-to-noise-ratio (SNR) regime of the SR–RD correlated channel scenario compared with the uncorrelated channel scenario. Finally, Monte Carlo simulations are performed to validate the theoretical results.